Improving Latino Health Equity Through Spanish Language Interpreter Advocacy in Kansas. (March 2019) - Showstack, Rachel E.; Guzman, Kelly; Chesser, Amy K.; Woods, Nikki Keene
Introduction: Federal law requires any agency receiving federal aid to take "reasonable steps" to provide meaningful access to qualified limited English proficient (LEP) individuals. However, policies for the provision of language access services, including medical interpretation, vary substantially by state. The Latino population and the number of LEP individuals in the U.S. state of Kansas have grown substantially over the past 20 years, necessitating increased attention to the state's language access policies. Method: Though a review of previous research, we present health disparities affecting Latinos in Kansas, examine the state's language access policies for health care, and argue that health disparities could be reduced through improved language access. Findings: While Kansas reimburses health care entities for interpreter services associated with Medicaid, the state has no health care interpreter competency requirements. As a result, LEP persons, primarily Spanish speakers, may be left to navigate through complex hospital systems with inadequate guidance in their language and may be at an increased risk for medical errors due to language barriers. Conclusion: We suggest changes that could be implemented to improve access and reduce health disparities affecting Latinos in Kansas and across the United States, and we describe work that is currently underway to support these changes.